2011
DOI: 10.2334/josnusd.53.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of histone modification on transcriptional regulation and HIV-1 gene expression: possible mechanisms of periodontal diseases in AIDS progression

Abstract: Although approximately 200 distinct cell types - including fibroblasts, neurons, and hematopoietic cells - possess the same DNA sequence, they have diverse functions in humans and exhibit considerably different gene expression patterns. It has become increasingly clear that epigenetic regulation plays an important role in gene expression. There are two major forms of epigenetic regulation: posttranslational modification of DNA-associated histone proteins in chromatin and methylation of DNA. These forms are reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 82 publications
0
35
0
1
Order By: Relevance
“…DNA methyl transferase 1 methylates cytosine residues in the DNA that attract DNA methyl-binding proteins, which in turn recruit histone deacetylases. These enzymes remove acetyl groups from the tails of histones, causing chromatin condensation that results in repression of gene transcription (65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methyl transferase 1 methylates cytosine residues in the DNA that attract DNA methyl-binding proteins, which in turn recruit histone deacetylases. These enzymes remove acetyl groups from the tails of histones, causing chromatin condensation that results in repression of gene transcription (65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…Resulting from the fermentation of indigestible food components by anaerobic commensal bacteria composing the gut microbiome (8-10, 14, 17, 19-24), SCFAs have been suggested to affect HIV-1-mediated disease progression (1)(2)(3)(4)(5)(6)(7)42). Previous studies have focused on the impact of the SCFA butyrate on reactivation of the provirus in cells latently infected with HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the impact of the SCFA butyrate on reactivation of the provirus in cells latently infected with HIV-1. It has been suggested that butyrate acts as an inhibitor of class I HDACs, leading to histone hyperacetylation and enhancement of HIV-1 gene transcription (2,3). Indeed, several lines of evidence indicate that HDACs in the total CD4 ϩ T cell population was evaluated by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…The contributing enzymes on methylation and acetylation specifically affect toward various histone proteins [55]. As the switch in on-off regulation of gene expression, lysine residues acetylation on histones is associated with gene activation, whereas methylation of lysine residues can result in either activation or silencing on gene expressions [56]. As an epigenetic mechanism, posttranslational modifications of histones are involved in the regulation of normal and disease-associated development.…”
Section: Histone Modificationmentioning
confidence: 99%